Booker T. Washington black leadership in the age of Jim Crow - Smock, Raymond W. (Dee, 2009)
Interprets the life of Booker T. Washington, exploring his rise from slavery to become an influential educator and African American leader.
Includes bibliographical references and index
Keywords: Washington, Booker T -- 1856-1915; Washington, Booker T. -- 1856-1915; Schwarze. USA; African Americans -- Biography; Educators -- United States -- Biography; USA; Biografie